PRIVATIZATION IN THE OIL SECTOR: STATE AND SUGGESTIONS - Candela, Edgardo (2001)
For many Peruvians, it has been clear that the state should leave the effort of economic growth to the private, domestic or foreign investment. The telecommunications sector continues its startup process and hopefully will give the competition a step shorter. The Osiptel has shown an unclear conduct its work regulator, seems to be focusing on the company, not end users or the market itself. So depend on the performance of the agency, exclusively from now on, that privatization of the sector benefits society as a whole: better prices, quality services and genuine competition. The task of promoting competition in the supply of fixed line service and subject to flat rate Internet service is pending.